2003
DOI: 10.1152/ajpregu.00588.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activated epidermal growth factor receptor (ErbB1) protects the heart against stress-induced injury in mice

Abstract: Acute, high-intensity stress induces necrotic lesions in the heart. We found that restraint-and-cold (4°C) exposure (RCE) raises plasma lactate dehydrogenase (LDH), creatine kinase (CK), and transaminase activity in a time-dependent manner, with a peak value 7 h after stimulus cessation. At 24 h, signs of necrotic lesions were observed in paraffin sections stained with hematoxylineosin: focal accumulation of mononuclear cells in subendocardial areas of the left ventricle wall and focal hemorrhage in papillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 55 publications
4
41
0
Order By: Relevance
“…We previously demonstrated that such a high EGF concentration protects the heart from suffering injury (42). Therefore, we studied next whether EGF has a similar role in the liver.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We previously demonstrated that such a high EGF concentration protects the heart from suffering injury (42). Therefore, we studied next whether EGF has a similar role in the liver.…”
Section: Resultsmentioning
confidence: 95%
“…In some experiments, mice were either sialoadenectomized or sham-operated (24) 1 wk before isolation. In another experiment, intruder mice received an intraperitoneal injection of the EGF receptor inhibitor tyrphostin AG-1478 (Calbiochem, Merck Eurolab, Granada, Spain) (0.25 mg/kg dissolved in 10% DMSO) 20 min before the experiment (42). In another experimental series, intruder mice received anti-EGF antibodies by either an sc injection of 0.15 ml of rabbit anti-mEGF serum 48 h before the experiment, or an intraperitoneal injection of 0.1 ml of rabbit anti-mEGF serum 2 h before the experiment.…”
Section: Aggressive Encountersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to date support protection via EGF, while TGF fails to protect against acute myocardial I-R injury (Manukyan et al, 2011), and exogenous HB-EGF has yet to be assessed. Injecting EGF (0.25 mg/kg) 20 min before exposing mice to the stress of restraint-and-cold exposure also reduces myocardial injury markers (Pareja et al, 2003), an effect abolished by AG1478. In isolated mouse hearts exogenous EGF protects against detrimental functional effects of continuous epinephrine stimulation (Lorita et al, 2002), with subsequent work showing EGF induces Tyr-phosphorylation of ErbB1 but not ErbB2, and protects against combined epinephrine/I-R injury (Lorita et al, 2009).…”
Section: Role In Adaptive Protection -Ischaemic Preconditioningmentioning
confidence: 95%
“…EREG produced a robust and dose-dependent increase in licking behavior that was indistinguishable from that (tyrphostin AG 1478; hereinafter, AG 1478; 10 mg/kg) and 2 clinically available (50 mg/kg gefitinib and 75 mg/kg lapatinib) EGFR tyrosine kinase inhibitors in a battery of algesiometric assays. Doses were chosen based on prior in vivo efficacy against stress-induced necrotic lesions in the heart (AG 1478) and in chemoprevention of lung cancer (gefitinib) or breast cancer (lapatinib) in mice (19)(20)(21). We first confirmed that none of the drugs, delivered systemically and at very high doses (AG 1478, 100 mg/kg; gefitinib, 300 mg/ kg; lapatinib, 300 mg/kg), produced significant ataxia over a 1-hour testing period on the rotarod ( Figure 1A).…”
Section: Modulation Of Egfr Affects Pain Sensitivity In Micementioning
confidence: 99%